Proceedings of FORM 2021 Construction The Formation of Living Environment - Akimov, Pavel; Vatin, Nikolai; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book gathers the latest advances, innovations, and applications in the field of environmental and construction engineering, as presented by international researchers at the XXIV International Scientific Conference "Construction: The Formation of Living Environment", held in Moscow, Russia on April 22-24, 2021. It covers highly diverse topics, including sustainable innovative development of the construction industry, building materials, reliability of buildings and constructions and safety in construction, modelling and mechanics of building structures, engineering and smart systems in construction, climate change and urban environment. The contributions, which were selected by means of a rigorous international peer-review process, highlight numerous exciting ideas that will spur novel research directions and foster multidisciplinary collaborations.
Chapter 1: Particles transport with deposit release in porous medium -- Chapter 2: Macrokinetic model of biochemical oxidation -- Chapter 3: Elastic-plastic equilibrium of a hollow ball made of inhomogeneous ideal-plastic material -- Chapter 4: Physically-based streamflow predictions in ungauged basin with semi-arid climate -- Chapter 5: Viscoelastic vibrations of a layered composite with internal friction.
Keywords: Buildings -- Design and construction; Fire prevention; Buildings -- Protection; Sustainability; Construction industry -- Management; Building Construction and Design; Fire Science, Hazard Control, Building Safety; Sustainability; Construction Management; Civil engineering -- Congresses; Construction industry -- Environmental aspects -- Congresses